Pengaruh Modal Psikologis dan Berbagi Pengetahuan terhadap Perilaku Kewargaan Organisasi dengan Komitmen Organisasi sebagai Mediator - Ahmat Tawio; Tehubijuluw Zacharias; Stanislaus Kostka Ohoiwutun (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study examines the impact of psychological capital and knowledge sharing on organizational citizenship behavior, with organizational commitment as a mediating factor, among employees of the Regional Civil Service and Human Resource Development Agency (BKPSDM) of West Seram Regency. The research adopts a quantitative approach with a correlational design. The population consists of all 20 employees, selected using a full sampling technique. Data were collected via a Likert-scale questionnaire. The findings reveal that psychological capital exerts a positive and significant influence on both organizational commitment and organizational citizenship behavior. Similarly, knowledge sharing positively and significantly affects organizational commitment and organizational citizenship behavior. Moreover, organizational commitment is found to partially mediate the relationship between psychological capital and knowledge sharing on organizational citizenship behavior. These results suggest that employees who possess strong psychological resources and actively participate in knowledge-sharing practices are more likely to develop stronger organizational commitment and demonstrate positive discretionary behaviors. Therefore, strengthening psychological capital and cultivating a knowledge-sharing culture are vital strategies for enhancing overall organizational effectiveness.